Hydrogel is Superior to Fibrin Gel as Matrix of Stem Cells in Alleviating Antigen-Induced Arthritis - Liu, He (Polymers (Basel), 2016)
Recently, therapy with bone marrow mesenchymal stem cells (BMMSCs) has been attempted to relieve rheumatoid arthritis (RA) and reconstruct cartilage injury. However, treatment has been unsuccessful in complete prevention of persistent cartilage destruction and resulted in inferior outcomes of cartilage regeneration. Scaffolds are an important construct in the field of cartilage tissue engineering, but their role in arthritis treatment has not yet been fully examined. Here, we transplanted two types of scaffold-assisted BMMSCs: fibrin gel- and poly(l-lactide-co-glycolide)−poly(ethylene glycol)−poly(l-lactide-co-glycolide) (PLGA−PEG−PLGA) hydrogel-assisted BMMSCs referred as FGB and HGB groups, respectively, into subchondral defects for the treatment of antigen-induced arthritis. The administration of exogenous BMMSCs ameliorated joint swelling and decreased both joint surface temperature and inflammatory cytokine levels in both groups. Immune cell composition of the inflammation of surrounding synovium, protection of adjacent cartilage, and improved cartilage repair were also observed. Overall, the HGB group had a better therapeutic efficacy than the FGB group. In conclusion, local transplantation of BMMSCs in subchondral defects presents a novel approach in inducing RA remission and recovery of RA-induced cartilage injury. To induce these changes, the selection of scaffold for cell support is exceedingly important. Further studies are needed regarding the treatment options of subchondral defects in arthritis based on modified scaffold development, application of defined MSCs sources, combination of pharmacotherapeutics, and the addition of factors that inhibit the processes of RA remission, promote the recovery of RA-induced cartilage injury and the relationship between these factors.